Multikultural Dan Pendidikan Multikultural di Universitas Negeri Medan - Purnamasari, Ika; Najuah, Najuah; Nasution, Muhammad Ardiman; Pakpahan, Ananda Dasiva (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesia has many different races, cultures, and religions. To prevent conflicts and conflicts, multicultural education that respects differences is needed. This will keep the diversity and richness of culture alive, which must be preserved. Every civilization and culture is in the same place in multicultural education. Helping students gain knowledge and respect for others who have different personality values, tribes, and cultures is the main goal of the concept of multicultural education. In dealing with multicultural education, four principles work together: pluralism, equality, tolerance, and democracy. Therefore, multicultural education is education that emphasizes a way of life that is respectful, sincere, and tolerant of cultural diversity in a society that has many variables.